θ-Almost summable sequences - Fatih Nuray (International Journal of Mathematics and Mathematical Sciences)
King[3] introduced and examined the concepts of almost A-summable sequence, almost conservative matrix and almost regular matrix By following King, in this paper we introduce and examine the concepts of θ-almost A-summable sequence, θ-almost conservative matrix and θ-almost regular matrix